Future Scenarios for CO2 Sequestration by Oil Palm in Southeast Asia Versus Other Regions to Reduce Climate Change - Paterson, Robert Russell Monteith (Southeast Asia Development Research, 2025)
Carbon dioxide (CO2) emissions from fossil fuels are a significant contributor to climate change. Concentrations of CO2 were in balance when emissions were controlled by the photosynthetic capabilities of organisms on land and in oceans. Palm oil is a valuable commodity, and vast plantations of oil palm (OP) have been created, especially in Malaysia and Indonesia, which have involved destroying rainforests and growing palms on peat soil, which increases CO2 emissions. However, OPs are effective at sequestrating CO2, and growing OPs on degraded land may allow sequestration to combat climate change. Future scenarios for CO2 sequestration are presented in this report by employing a CLIMEX computer programme, climate models, and narratives to determine optimal future sequestration. High levels of CO2 sequestration by OP will be maintained generally until 2070, but this will decrease dramatically by 2100. Parts of Malaysia and Indonesia will have significantly greater sequestration than others. Some novel regions of high sequestration may occur in Paraguay and Uganda. Overall, it cannot be assumed that the OP will continue to sequester CO2 in the same places where it currently grows well. The modelling provides a basis for making decisions regarding where to grow OP for CO2 sequestration in the future. More modelling of future OP growth is required, focusing on the CO2 sequestration potential.